Evaluasi Penerapan Sistem Informasi Khanza Menggunakan Metode HOT-FIT Di Rumah Sakit Tentara Reksodiwiryo Kota Padang - Kamal, Syamsul; Mardi, Yuli; Regina, Regina (Akademi Perekam dan Informasi Kesehatan Imelda, 2024)
The transformation of changes from Manual Medical Records to Electronic Medical Records by the Government has been stipulated by the Minister of Health by issuing and stipulating Permenkes Number 24 of 2022 concerning Electronic Medical Records, in Permenkes no 24 of 2022 all Health Facilities will be implemented at the end of December 2023.Simkes Khanza is one of the Electronic Medical Record (RME) Health Management Information System Application programs that can be used by Hospitals, Clinics, PUSKESMAS, as well as Independent Practices that are open in nature, the Khanza Program is a program for Hospital Information Systems designed so that the home hospitals in managing management and processing hospital data can make reports properly and correctly. In carrying out data processing, the method used is the HOT-FIT method where this method is a theoretical framework model used to evaluate information systems in the field of health services.The purpose of this research is how much the benefits and programs of Khanza are in the Reksodowiryo Army Hospital, Padang City. From the results of research data processing consisting of 20 sample questionnaires with 32 questions obtained which were distributed and discussions with hospital staff, it was found that the use of the system in humans was a score of 64.83%, an average of 3 and a TCR of 81.4 which means that the human variable in using the system khanza, , User Satisfaction, trouble-free, user-friendliness means very good. Furthermore, for the organizational variable, the score was 64.83%, the average was 3.2 and the TCR was 81 with very good results. Then for the Technology variable, the score was 66.3%, the average was 3.3 and the TCR was 82.9 with very good results. Furthermore, the Benefit variable score is 65.3%, the average is 3.3 and the TCR is 81.9 with very good results. It can be concluded that the Khanza program is really needed in RST. Reksodowiryo City of Padang.